Back to the Futurists : the avant-garde and its legacy. - Adamowicz, Elza (Manchester University Press, 2015)
In 1909 the Italian poet Filippo Tommaso Marinetti's Founding Manifesto of Futurism was published on the front page of Le Figaro. Between 1909 and 1912 the Futurists published over thirty manifestos, celebrating speed and danger, glorifying war and technology, and advocating political and artistic revolution. This collection of essays aims to reassess the activities of the Italian Futurist movement from an international and interdisciplinary perspective, focusing on its activities and legacies in the field of poetry, painting, sculpture, theatre, cinema, advertising and politics. The essays offer exciting new readings in gender politics, aesthetics, historiography, intermediality and interdisciplinarity. They explore the works of major players of the movement as well as its lesser-known figures, and the often critical impact of Futurism on contemporary or later avant-garde movements such as Cubism, Dada, and Vorticism. The publication will be of interest to scholars and students of European art, literature and cultural history, as well as to the informed general public.